Perinatal compromise contributes to programming of GABAergic and glutamatergic systems leading to long‐term effects on offspring behaviour. (9th December 2019) - Shaw, Julia C.; Crombie, Gabrielle K.; Zakar, Tamas; Palliser, Hannah K.; Hirst, Jonathan J.
Abstract: Extensive evidence now shows that adversity during the perinatal period is a significant risk factor for the development of neurodevelopmental disorders long after the causative event. Despite stemming from a variety of causes, perinatal compromise appears to have similar effects on the developing brain, thereby resulting in behavioural disorders of a similar nature. These behavioural disorders occur in a sex‐dependent manner, with males affected more by externalising behaviours such as attention deficit hyperactivity disorder (ADHD) and females by internalising behaviours such as anxiety. Regardless of the causative event or the sex of the offspring, these disorders may begin in childhood or adolescence but extend into adulthood. A mechanism by which adverse events in the perinatal period impact later in life behaviour has been shown to be the changing epigenetic landscape. Methylation of the GAD1/GAD67 gene, which encodes the key glutamate‐to‐GABA‐synthesising enzyme glutamate decarboxylase 1, resulting in increased levels of glutamate, is one epigenetic mechanism that may account for a tendency towards excitation in disorders such as ADHD. Exposure of the fetus or the neonate to high levels of cortisol may be the mediator between perinatal compromise and poor behavioural outcomes because evidence suggests that increased glucocorticoid exposure triggers widespread changes in the epigenetic landscape. This review summarises the current evidence and recent literature about the impact of various perinatal insults on the epigenome and the common mechanisms that may explain the similarity of behavioural outcomes occurring following diverse perinatal compromise.